Kekerasan Simbolik Era Digitalisasi Terhadap Perilaku Masyarakat Beragama Di Desa Tanen Kecamatan Rejotangan Kabupaten - Wakhidatus Zahro’un Nihlah; Sindi Kania; A Zahid (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2023)
With the development of social media in Indonesia, it is easier for everyone to channel opinions through internet networks. Many things can be obtained besides channeling opinions, for example as a space for information, education, politics, da'wah, entertainment, health and so on. The era of digitalization is one sign of the development of globalization in the field of technology that displays the face of novelty and sophistication by providing convenience for users. This study aims to determine the symbolic violence of the digitalization era on the behavior of religious communities in Tanen Village and the causal relationship it causes. This research method uses descriptive qualitative research with observation techniques and interviews with several religious communities in Tanen Village by linking the results of the analysis and previous research using Pierre Bourdieu's theory of symbolic violence. The results of this study indicate that with the advancement of this digital era, the religious community in Tanen Village experienced symbolic violence as evidenced by some of the behavior of the people in Tanen Village, Rejotangan District. Evidence of symbolic violence experienced by the community is shown by the behavior of the people of Tanen Village behavior in social media but is not based on religious guidance.